Syndromes and Disorders Associated with Omphalocele (I): Beckwith-Wiedemann Syndrome - Chih-Ping Chen (Elsevier, 2007)
Beckwith-Wiedemann syndrome (BWS, OMIM 130650) is characterized by macrosomia, macroglossia, visceromegaly, hemihypertrophy, abdominal wall defects, ear creases/pits, neonatal hypoglycemia, polyhydramnios, placentomegaly, placental mesenchymal dysplasia, cardiac defects, nevus flammeus, hemangiomata, and an increased frequency of embryonal tumors. This article provides an overview of BWS including the genetics, genetic diagnosis, genotype/epigenotype-phenotype correlations, association with assisted reproductive technology, and prenatal diagnosis. Omphalocele is an important sonographic marker for BWS. Prenatal detection of omphalocele, fetal overgrowth, polyhydramnios, increased abdominal circumference, placentomegaly and/or placental mesenchymal dysplasia should alert one to the possibility of BWS and prompt a genetic investigation and counseling for BWS.